Soviet military intervention in Hungary, 1956 - Györkei, Jenő; Horváth, Miklós, 1953- (Atlantic studies on society in change, 1999)
"This first detailed account of Soviet military operations is based on access to unpublished material in Soviet archives, which have recently been reclassified." "The major contribution made by the book is its source material, which reveals new information on the organization, command, strategy, and tactics of the Soviet armed forces which invaded Hungary in 1956. Particularly interesting is the precise documentation of the irrationally large size of the forces. The volume is based on research in Soviet archives, and this alone makes it of unique scholarly importance."--Jacket